Stepwise approach in the management of penile strangulation and penile preservation: 15-year experience in a tertiary care hospital. Issue 4 (2nd October 2019) - Puvvada, Sandeep; Kasaraneni, Priyatham; Gowda, Ramesh Desi; Mylarappa, Prasad; T, Manasa; Dokania, Kanishk; Kulkarni, Abhishek; Jayakumar, Vivek
ABSTRACT: Objective : To present our stepwise approach to the management of penile strangulation and penile preservation with 15 years' experience in a tertiary care hospital, as penile strangulation is a rare urological emergency that requires immediate attention. Patients and methods : A prospective observational study was performed from March 2003 to December 2018 of patients presenting with penile strangulation to our hospital. Results : Nine patients with penile strangulation presented to us between March 2003 and December 2018. The most common motive for the application of a foreign body was sexual gratification (four patients). Three of the nine patients had a mental disorder. Objects used for strangulation included: metallic nut (three), metallic ring (two), plastic bottle (two), wooden hole (one), hammer head (one), and horse hair to control bleeding during circumcision (one). Most of the foreign bodies were located in the proximal penile region. The mean operative time was 38 min and three of the nine patients had complications. Conclusions : Penile strangulation is one of the rare urological emergencies experienced by a urologist. Removal of the foreign body can be difficult and there is no universal method of removal, as each case differs. So, following our stepwise approach can aid in removal of foreign body quickly and preserve the penis from fatal outcomes. Urologist should be aware of all the available armamentarium used for the removal of such foreign bodies. Abbreviation : SPC: suprapubic cystostomy